Meditation and Music Therapy in the Era of Digitalization: Challenges and Future Considerations - Li, Yingfei; Liu, Yanyan; Yuan, Ruikai; Zhang, Hailong (Journal of Posthumanism, 2025)
The integration of therapeutic meditation and music therapy has long been recognized for its profound impact on mental health, emotional well-being, and cognitive functioning. In the era of digitalization, these traditional practices are undergoing a transformative evolution, driven by advancements in artificial intelligence, virtual reality, and mobile health technologies. This perspective explores the intersection of meditation and music therapy with digital tools, highlighting both the opportunities and challenges presented by this technological shift. While digital platforms like meditation apps and VR-based music therapy offer unprecedented accessibility, personalization, and scalability, they also raise critical concerns regarding data privacy, the loss of humanistic care, and the potential commercialization of therapeutic practices. This paper examines the current landscape of digital meditation and music therapy, emphasizing the need for a balanced approach that integrates technological innovation with the core principles of empathy, cultural sensitivity, and scientific rigor. By proposing a comprehensive framework that considers the perspectives of patients, therapists, and technology, this study aims to guide the future development of digital therapeutic interventions, ensuring they remain effective, ethical, and inclusive in promoting mental health and well-being.